Research and control of network carbide in GCr15 bearing steel. (13th January 2020) - Huo, Xiangdong; Ning, Yuliang; Li, Liejun; Lv, Zhiwei; Chen, Songjun
Abstract: Due to the small amount of transformation during the phase transformation process, it is difficult to determine the phase transition temperature of the proeutectoid cementite in the bearing steel by the expansion method. In this paper, the Gleeble3800 thermal simulator was used to study the phase transformation behavior of GCr15 bearing steel at different cooling rates. Firstly, the phase transformation temperature range of pearlite is about 550 °C ∼ 700 °C measured by expansion method. Based on this, the transformation temperature range of proeutectoid cementite is about 700 °C ∼ 900 °C studied by metallographic method; The precipitation curve of proeutectoid cementite was supplemented, and the complete continuous cooling phase transition curve (CCT curve) of bearing steel was drawn. On this basis, the scheme of inhibiting the formation of proeutectoid cementite by two-stage cooling process was proposed and discussed, and the finishing cooling temperature was studied, which provides a basis for controlling network carbide in field production.